Ship representations on Mycenaean pottery; A rare depiction of a shipwreck from Koukounaries on Paros - Spanos, Stefanos (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
A deep bowl from Koukounaries on Paros offers a rare representation of a ship. The vessel is depicted upside down, making it a a unique depiction of a Mycenaean shipwreck. This Paros depiction may be compared to the representation of ships from Skyros and Tragana. The representation is more similar to shipwreck scenes such as the one on the north wall of the Great Temple of Medinet Habu. The possibility that the ship is an enemy ship will be discussed. Koukounaries had important overseas connections with the other Cycladic Islands, which lie at the crossroads of maritime trade with Asia Minor, Egypt, Syria, Cyprus and Crete.